2011
DOI: 10.1089/ten.tea.2010.0716
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mesenchymal Stromal Cell–Hyaluronic Acid Hydrogel Constructs on Immunophenotype of Macrophages

Abstract: During the past several years, multipotent mesenchymal stromal cells (MSCs) have rapidly moved from in vitro and animal studies into clinical trials as a therapeutic modality potentially applicable to a wide range of disorders. It has been proposed that ex vivo culture-expanded MSCs exert their tissue regeneration potential through their immunomodulatory and anti-inflammatory properties, and paracrine effects more than their ability to differentiate into multiple tissue lineages. Since extracellular matrix (EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
62
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 43 publications
6
62
0
Order By: Relevance
“…activation following culture with bone marrow-derived MSC, indicating an anti-inflammatory effect. 11,21 In this study, we demonstrated a similar effect when co-cultured with ADSC, with no statistical difference between abdominal and breast adipose tissues. Clinically, both CD16 and HLA-DR are measures of acute inflammation, particularly in systemic disease and trauma; reduction in these markers on circulating macrophages may be an indication in the resolution of inflammation.…”
Section: Discussionsupporting
confidence: 68%
“…activation following culture with bone marrow-derived MSC, indicating an anti-inflammatory effect. 11,21 In this study, we demonstrated a similar effect when co-cultured with ADSC, with no statistical difference between abdominal and breast adipose tissues. Clinically, both CD16 and HLA-DR are measures of acute inflammation, particularly in systemic disease and trauma; reduction in these markers on circulating macrophages may be an indication in the resolution of inflammation.…”
Section: Discussionsupporting
confidence: 68%
“…hASCs contributed to adipose regeneration through direct differentiation and/or paracrine action. As others have posited [2729, 3335], we believe that hASCs and DSAF worked synergistically to activate M2 polarization and provide a pro-regenerative environment for adipose tissue formation in our model. Hence, our data suggest that the hASCs-DSAF 3D scaffold holds great promise in soft tissue engineering because each component not only directly participates in adipose tissue regeneration but also modulates the host immune response to the engineered constructs.…”
Section: Discussionsupporting
confidence: 59%
“…For example, certain surface peptides and ligands on the scaffold that have been exposed by the decellularization process may modulate the immune response [28, 3032], and the ECM degradation products may have immunomodulatory activity [26]. hASCs, owing to their unique immunomodulatory properties, can also induce the M2 macrophage phenotype [33, 34]. One recent study suggested that 3D topography plays a key role in regulating mesenchymal stem cells’ immunomodulatory effects, which can push macrophages towards an anti-inflammatory phenotype [35].…”
Section: Discussionmentioning
confidence: 99%
“…In pre-clinical investigations, bone marrow mesenchymal stromal cell (BM-MSC) and hyaluronic acid hydrogel therapies have shown promise for vocal fold regeneration through enhanced tissue viscoelasticity, extracellular matrix (ECM) profiles, and immunomodulation [310]. Prior to the development of a cell and/or gel-based therapy for clinical use, a number of practical considerations need to be addressed.…”
Section: Introductionmentioning
confidence: 99%